Community Health Creation: Developing and Applying the Health Creation Index to Evaluate a Community Walking Programme (Baltic Journal of Sport and Health Sciences, 2026)
Physical inactivity remains a pressing public health issue in Europe, with a disproportionate impact on populations facing health inequalities. Health creation – defined as enabling the conditions for individuals to achieve physical, mental, and social wellbeing – calls for innovative and inclusive measurement tools. This study introduces the Health Creation Index (HCI), a novel composite measure capturing modifiable individual, social, and environmental contributors to wellbeing.To demonstrate the utility of the HCI, we applied it to evaluate the impact of Beat the Street (BTS), a gamified, community-wide walking and active travel programme. Pre- and post-intervention data were analysed for 22,350 BTS participants, of whom 73% were female, 16% lived in the most deprived areas (IMD 1–2), 6% were aged 60+, and 19% reported long-term health conditions. Matched post-intervention data were available for 5,885 individuals.At baseline, 54% of participants met the Active Lives Survey criteria for physical activity. After the intervention, 13% had moved from inactive to active status. HCI scores improved by 2.5% among these newly active individuals, compared to a 1.5% average increase across all participants. Lower HCI scores were recorded among people with disabilities (3.49/5), and higher scores among women (3.75/5). Participants who were active at baseline consistently showed higher HCI scores than their inactive counterparts (p < 0.01).These findings highlight the potential of walking-based community interventions to enhance protective factors for health creation and reduce wellbeing disparities. The HCI offers a practical framework to identify those most in need and to guide inclusive, place-based strategies in physical activity promotion.